2017
DOI: 10.5812/iranjradiol.56033
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Diffusion-Weighted Magnetic Resonance Imaging in the Follow-Up of Uncomplicated Acute Appendicitis: Initial Results

Abstract: Background: Several studies have shown that the majority of patients with simple appendicitis can be treated effectively and safely with antibiotics, avoiding unnecessary operation. Objectives: The objective of this study was to assess the role of diffusion-weighted imaging (DWI) in the follow-up of conservative treatment of simple appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We identified 12 studies that reported on topics unrelated to diagnostic accuracy. 5 , 50 60 These studies are summarised in Table 4 : three reported on trends of MRI use, 51 , 53 , 55 two were reports about visualisation of the normal appendix, 58 , 59 two were analyses of financial implications, 5 , 60 one was a secondary study comparing simple versus perforated appendicitis using different imaging modalities, 50 one reported on MRI to assess treatment response in non-operatively managed appendicitis, 52 one was a decision analysis, 56 one was a radiologist training report, 57 and one was a survey of imaging prioritisation. 54 …”
Section: Resultsmentioning
confidence: 99%
“…We identified 12 studies that reported on topics unrelated to diagnostic accuracy. 5 , 50 60 These studies are summarised in Table 4 : three reported on trends of MRI use, 51 , 53 , 55 two were reports about visualisation of the normal appendix, 58 , 59 two were analyses of financial implications, 5 , 60 one was a secondary study comparing simple versus perforated appendicitis using different imaging modalities, 50 one reported on MRI to assess treatment response in non-operatively managed appendicitis, 52 one was a decision analysis, 56 one was a radiologist training report, 57 and one was a survey of imaging prioritisation. 54 …”
Section: Resultsmentioning
confidence: 99%